Penerapan Motif Buketan Kamboja Bali Pada Make Up Fantasi Mitologi Yunani Dewi Alam Baka - Cyrilla luthfi, Azarine (Universitas Negeri Jakarta, 2023)
The character's makeup resembles a bouquet of Balinese frangipani on the Greek mythology fantasy makeup of the goddess of the afterlife; this Balinese frangipani exudes an elegant aura inspired by Persephone. Makeup seems to have a charming aura when worn with a fashion design. Before creating a fashion design, it must align with the mood board so that the clothes and facial makeup reflect the theme. The makeup can then be analyzed as follows: Center of interest: what is intended by the style from Balinese Bouquet Motifs. Focal point: the center point of the makeup is the addition of the red-orange color. Harmony hue: the selection of eyeshadow colors using a harmonious color. Axial balance: there is a balance of Balinese Buketan motifs on the right and left faces, even though the sizes in the two images are symmetrically the same. Rhythm: there is a repetition of the Balinese Bouquet motif with line patterns. Repetition: There is a repetition of frangipani flowers and tiles. Cambodian makeup, Fantasy Buketan, and Cambodian Balinese motifs exude an aura of elegance and fantasy mythology. Clothing includes models like fantasy dresses and millennial accessories, such as headpieces, which further reinforce the concept of Persephone, the goddess of death.